Reconstructing gene regulatory network with enhanced particle swarm optimization - Sultana, Rezwana; Showkat, Dilruba; Samiullah, Md.; Chowdhury, Ahsan Raja Aja (© 2014 Springer International Publishing Switzerland, 2016)
This conference paper was presented in the 21st International Conference on Neural Information Processing, ICONIP 2014; Kuching; Malaysia; 3 November 2014 through 6 November 2014 [© Springer International Publishing Switzerland 2014]